Ascomycetous Yeasts Associated with Naturally Occurring Fruits in a Tropical Rain Forest - Prada, G. M M; Pagnocca, F. C. [UNESP] (Springer Nature, 1997)
Fruits from twenty different species of angiosperms were collected during the period from November, 1991 to January, 1992. Two hundred and two strains of yeasts and yeast-like fungi were isolated, of which 74 % showed ascomycetic affinity. Candida was the predominant genus, followed by (in descending order of occurrence): Cryptococcus, Klœckera, Sporobolomyces, Pichia, Hanseniaspora and Bullera. Black yeasts and other strains showing basidiomycetic affinity were also isolated. The genus Candida represented the highest number of identified species and the greatest variety of associated substrates. Among the ascomycetes and their anamorphs, 38 species were identified, with Klœckera apiculata being the most frequent among the isolates and the one which occurred in the largest variety of substrates. Some of the biotypes designated as Candida sp. A, B, C, D, E, F, G, H, I, and Pichia sp. did not correspond to the standard species description found in the literature, and may represent new species. The strains of yeasts isolated in this study were characterized and incorporated into the Tropical Culture Collection of the Fundação Tropical de Pesquisas e Tecnologia André Tosello, Campinas, São Paulo.
Keywords: Ascomycetes; Brazil; Candida; classification; comparative study; ecosystem; fruit; isolation and purification; microbiology; species difference; tropic climate; Ascomycota; Ecosystem; Fruit; Species Specificity; Tropical Climate